Scaling up local carbon action: the role of partnerships, networks and policy. Issue 4 (4th July 2014) - Hamilton, Jo; Mayne, Ruth; Parag, Yael; Bergman, Noam
Abstract : The transition to a low-carbon society is imperative to climate change mitigation and requires cross-sectoral action at multiple levels. A growing literature emphasizes local action, but less is written about scaling up action at a county level. Combining three analytical perspectives – transition theory, strategic niche management and the middle-out – we examine the evolution and scaling up of local community-scale carbon action in Oxfordshire county. Our analysis is based on four local-level research projects. By identifying the roles and strategies of local actors in the development and scaling up of low carbon innovation and action, we conclude that local meso-level actors are crucial for catalyzing initial stages of county-level transitions, but limited in their capacity to scale up low-carbon innovation.